Wearable Patch ECG monitors and transesophageal electrophysiological study for diagnosing palpitations of unknown origin - Yang, Ruike; Yang, Lihong; Zhang, Qiang; Wang, Shuhui; Xu, Jinyi (Frontiers in Cardiovascular Medicine, 2024)
Objective To analyze the application value of wearable adhesive Patch ECG monitors (Patch ECG monitors) combined with Transesophageal Electrophysiological Study (TEPS) in the diagnosis of palpitations of unknown origin. Methods Patients with suspected arrhythmia who were admitted to Henan Provincial People's Hospital between October 2021 and July 2023 due to recurrent paroxysmal palpitations of unknown origin, with or without accompanying symptoms such as dizziness, amaurosis, and syncope, were included in the study. All patients underwent TEPS. Those who did not exhibit arrhythmia during the TEPS were selected for Patch ECG monitoring, which lasted several weeks (depending on the duration of the symptom capture). The results of TEPS, Patch ECG monitors, and clinical diagnoses were observed and recorded. Sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) of TEPS alone, Patch ECG monitoring in patients with negative TEPS results, and in combination of both methods for diagnosing palpitations of unknown origin were analyzed based on clinical diagnostic outcomes. Results A total of 569 patients were included in this study. The TEPS results exhibited that 227 of the 569 patients did not detect arrhythmias and 342 detected arrhythmias. Of the 569 patients, 102 refused to undergo Patch ECG monitors, and 467 patients completed the entire study process. Among them, 379 cases (66.61%) were clinically diagnosed as arrhythmias. TEPS shows good performance in most evaluation indices except negative predictive value (NPV) (69.60%, 95% CI, 61.54%-77.66%). The combined diagnosis was strongly consistent with the clinical diagnosis. The accuracy, sensitivity, and NPV of TEPS combined with Patch ECG monitors in the diagnosis of palpitations of unknown origin were significantly higher than those of TEPS alone. Conclusion Wearable adhesive patch ECG monitors combined with TEPS can enhance the diagnostic efficiency of palpitations of unknown origin.